Effects of Acute Confinement Stress-induced Hypothalamic-pituitary Adrenal Axis Activation and Concomitant Peripheral and Central Transforming Growth Factor-β1 Measures in Nonhuman Primates. (February 2017) - Coplan, Jeremy D.; Gopinath, Srinath; Abdallah, Chadi G.; Margolis, Jeffrey; Chen, Wei; Scharf, Bruce A.; Rosenblum, Leonard A.; Batuman, Olcay A.; Smith, Eric L. P.
Transforming growth factor-β1 (TGF-β1) is a multifunctional cytokine with anti-inflammatory, immunosuppressive, and neuroprotective properties. The hypothalamic-pituitary-adrenal axis and immune system exert bidirectional influences on each other, via cortisol and TGF-β1, but the exact nature of the interaction is not well characterized. The current study examined the effects, in bonnet macaques ( Macaca radiata ), of two consecutive acute confinement stress periods in an unfamiliar room while mildly restrained, first without and then with dexamethasone pretreatment (0.01 mg/kg intramuscular). Preceding the confinement studies, a non-stress control condition obtained contemporaneous levels of cortisol and TGF-β1 in both plasma and cerebrospinal fluid to match the confinement stress studies. Subjects were reared under either normative or variable foraging demand conditions. Since there were no rearing effects at baseline or for any of the conditions tested—either for cortisol or TGF-β—the study analyses were conducted on the combined rearing groups. The stress condition increased both plasma and cerebrospinal fluid cortisol levels whereas dexamethasone pretreatment decreased cortisol concentrations to below baseline levels despite stress. The stress condition decreased TGF-β1 concentrations only in cerebrospinal fluid but not in serum. Together, the data suggested that stress-induced reductions of a centrally active neuroprotective cytokine occur in the face of hypothalamic-pituitary-adrenal axis activation, potentially facilitating glucocortoid-induced neurotoxicity. Stress-induced reductions of neuroprotective cytokines prompt exploration of protective measures against glucocorticoid-induced neurotoxicity.